Study on acetylcholinesterase inhibitor derived from Datura metel L. / Hani Shuhaireen Mohamad Hanafiah - Hani Shuhaireen , Mohamad Hanafiah (2017)
Datura metel Linn locally known as kecubung, contains flavonoid, phenols and numerous alkaloid in the leaves, stem and seeds. These chemical constituents are fundamental in the anticholinergic treatment of Alzheimer’s disease (AD). Anticholinesterase enhances the concentration of cholinergic neurotransmitters which is lacking in AD. To date, no in vitro study of acetylcholinesterase inhibitory activity of D. metel’s parts has been published. This research analyses D. metel’s anticholinesterase inhibitory properties and its neurobehavioral effect utilising mice model. The TLC results showed intense presence of alkaloids in the leaves. The highest concentration of flavonoid in the seeds chloroform extract was 286.8939 mg QE / g while the highest total phenol contents found in leaves, 305.1163 mg GAE / g. LCMS/MS had been used to analyse alkaloid types in leaves which detected 3-hydroxy-6-tigloxtropane, apoatropine, cuscohygrine, daturalactone, daturalin ammonium, adduct homatropine, hyoscyamin, scopolamine, tannin, tropan alkaloids and withalactone. Alkaloids detected in the stem were anisodamine, apoatropine, hyoscymine, meteloidine, proanthocyanidin and scopolamine, whereas alkaloids found in the seed were anisodamine, into, proanthocynidin and scopolamine. Ellman’s method was used to quantify AChEI activity of leaves, stem and seeds methanol extracts. Of all the extracts, leaves had the highest inhibition of 75.94 % at 150 μg / ml extract concentration. From the Brine Shrimp Lethality Assay, LC50 of leaves extract were 311.228 μg / ml and non-toxic. Animal study using the number of repeat entries to arms of the maze was designed to investigate the impact of leaves methanol extract on valium-impaired mice memory. Leaves extract were given via oral gavage. The group of mice administered with leaves methanol extract showed less number of repeated entries to arm maze in both genders. These research findings are inferred to propose the use of natural acetylcholinesterase inhibitors from D. metel as a potential treatment for Alzheimer’s disease.